(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Principle of working of the system is heating the saline water using PTSC and control the water flow through EP. Using SU system salt water. Finally the condenser into the CU give the distillate output. When the lower flow rate attained the highest evaporation system then automatically enhanced the productivity of the still. It shows 6 L/h, achieved 92◦C. Best performance of the distiller attained by 7.5 L/h - 44.7 L/daytime and 59.6%. Cost of water is 0.0085 /L.